Krisis Remaja dan Media Massa di Malaysia : Suatu Tinjauan dari Perspektif Islam - Abd. Rahim, Rahimin Affandi (Jurnal Usuluddin, 1999)
This article emphasizes the question on Malaysian teenagers moral which divided into two section, i.e (i) the influence of westernization on the Malay society before and after independence (ii) current deterioration of moral values due to the involvement of mass media. Finally, this article also mentions the participation of various government agency and NGOs to overcome the above moral deterioration.